(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
The Indigenous Peoples Rights Act of 1997 codified the use of Indigenous Peoples as reference to the ethnic minorities of the Philippines. Government officials and volunteers from the non-governmental organizations [NGOs], and the academic institutions, however, use the term Lumad as a reference to all ethnic minorities in Mindanao that share no common narrative. This paper is a case study exploring the lifestyles, and culture of the Subanens of Guimad, Ozamiz City, and whether they befit the existing Lumad Narratives. The use of term Lumad as reference to the Subanens of Guimad, Ozamiz City and all other ethnic minorities should be evaluated in order to guarantee that the distinct diverse identities, and cultures of these ethnic minorities are not reduced into a common, singular narrative.